Basic Science Faculties: A Rising Problem - Sharma, Anup (Journal of Nepalgunj Medical College, 2023)
In the entire four and half year’s course of MBBS, basic science, the first two years is a part where the foundation of a future doctor is laid. Like in any other school, college or a university, in MBBS also the teachers play an important role. It is obvious that without them no school, college or a university can run.